Konsepsi Sosio Kultural Etnis Jawa dan Madura di Eks-Karesidenan Besuki tentang Pangan - . Nawiyanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article discusses the sosio-cultural conceptions of foodcrops and foodstuffs among Javanese and Madurese ethnic groups. Drawing upon historical and anthropological materials, it explores views, knowledge, and beliefs concerning especially rice among the Javanese and corn (maize) among the Madurese in the former residency of Besuki. For the two ethnic groups, foodstuffs have not only physiological functions, but also cultural ones. The socio-cultural conceptions of food crops and foodstuffs, however, are far richer among the Javanese ethnic group than among the Madurese. Especially with the launching of the green revolution program, there has been a great shift in food crops production and staple food consumption among the Madurese from maize to rice. Apart from practical reason, a combination of ecological, economical, and sociological factors help to understand this shift.